Respuesta :

Since, by definition, [tex]i^2=-1[/tex], we deduce that [tex]\sqrt{-1}=i[/tex]

So, we have

[tex]2\sqrt{-16}+\sqrt{-9}=2\sqrt{-1\cdot 16}+\sqrt{-1\cdot 9}=2+\sqrt{-1}\sqrt{16}+\sqrt{-1}\sqrt{9}=2\cdot i\cdot 4+3i=8i+3i=11i[/tex]

Answer:

11i

Step-by-step explanation:

These roots are imaginary, but let's make it so that i=the square root of -1. simplify the two roots to get 4i and 2i. Multiply the 4i by 2 to get 8i. add them together to get 11i

TL;DR

2x4i+3i

8i+3i

11i

ACCESS MORE